Southern Extension to the Breeding Range of the Gyrfalcon, Falco Rusticolus, in Eastern North America - Brodeur, S.; Morneau, F.; Décarie, R.; DesGranges, J.-L.; Negro, J. (ARCTIC, 1995)
We report the observation of four gyrfalcon (Falco rusticolus) nests and several adults south of the previously recognized southern limit of the species' breeding distribution in eastern North America. Our southernmost observations extends the known breeding range approximately 400 km to the south. The northern forest tundra biome could delineate the southern limit to the breeding range of the gyrfalcon. Nous rapportons la découverte de quatre nids de faucon gerfaut et la mention de quelques adultes au sud de la limite connue de l'aire de reproduction de l'espèce dans l'est de l'Amérique du Nord. Notre observation la plus méridionale étend l'aire de répartition quelques 400 km plus au sud. Les limites sud de la toundra forestière septentrionale pourraient coincider avec celle de l'aire de reproduction du faucon gerfaut.Mots clés: faucon gerfaut, nicheur, répartition, Baie d’Hudson, Québec.